Reduced fucosylation in the distal intestinal epithelium of mice subjected to chronic social defeat stress - Omata, Yasuhiro; Aoki, Reiji; Aoki-Yoshida, Ayako; Hiemori, Keiko; Toyoda, Atsushi; Tateno, Hiroaki; Suzuki, Chise; Takayama, Yoshiharu (Scientific reports, 2018)
Psychological stress can cause dysfunction of the gastrointestinal tract by regulating its interaction with central nervous system (brain-gut axis). Chronic social defeat stress (CSDS) is widely used to produce a rodent model of stress-induced human mood disorders and depression. We previously showed that CSDS significantly affects the intestinal ecosystem including cecal and fecal microbiota, intestinal gene expression profiles and cecal metabolite profiles. Here, we investigated whether the glycosylation pattern in the intestinal epithelium was affected in C57BL/6 mice exposed to CSDS (hereinafter referred to as CSDS mice). A lectin microarray analysis revealed that CSDS significantly reduced the reactivity of fucose-specific lectins (rAOL, TJA-II, rAAL, rGC2, AOL, AAL, rPAIIL and rRSIIL) with distal intestinal mucosa, but not with mucosa from proximal intestine and colon. Flow cytometric analysis confirmed the reduced TJA-II reactivity with intestinal epithelial cells in CSDS mice. In addition, distal intestine expression levels of the genes encoding fucosyltransferase 1 and 2 ( Fut1 and Fut 2) were downregulated in CSDS mice. These findings suggest that CSDS alters the fucosylation pattern in the distal intestinal epithelium, which could be used as a sensitive marker for CSDS exposure.